Content and delivery preferences for information to support the management of high blood pressure - Chapman, N.; Marques, F. Z.; Picone, D. S.; Adji, A.; Broughton, B. R. S.; Dinh, Q. N.; Gabb, G.; Lambert, G. W.; Mihailidou, A. S.; Nelson, M. R.; Stowasser, M.; Schlaich, M.; et al. (Journal of human hypertension, 2024)
Blood pressure(BP) management interventions have been shown to be more effective when accompanied by appropriate patient education. As high BP remains poorly controlled, there may be gaps in patient knowledge and education. Therefore, this study aimed to identify specific content and delivery preferences for information to support BP management among Australian adults from the general public. Given that BP management is predominantly undertaken by general practitioners(GPs), information preferences to support BP management were also ascertained from a small sample of Australian GPs. An online survey of adults was conducted to identify areas of concern for BP management to inform content preferences and preferred format for information delivery. A separate online survey was also delivered to GPs to determine preferred information sources to support BP management. Participants were recruited via social media. General public participants ( n = 465) were mostly female (68%), >60 years (57%) and 49% were taking BP-lowering medications. The management of BP without medications, and role of lifestyle in BP management were of concern among 30% and 26% of adults respectively. Most adults (73%) preferred to access BP management information from their GP. 57% of GPs (total n = 23) preferred information for supporting BP management to be delivered via one-page summaries. This study identified that Australian adults would prefer more information about the management of BP without medications and via lifestyle delivered by their GP. This could be achieved by providing GPs with one-page summaries on relevant topics to support patient education and ultimately improve BP management.